Treatment of premature calves with clinically diagnosed respiratory distress syndrome - Karapinar, T.; Dabak, M. (Blackwell Publishing, 2008)
Background: Respiratory distress syndrome (RDS) has been reported previously in premature calves. However, there have been no published data on the effect of surfactant replacement therapy in the treatment of premature calves with RDS. Hypothesis: Surfactant replacement therapy added to the standard treatment for premature calves clinically diagnosed with RDS would increase the viability of the calves. Animals: Twenty-seven premature calves with clinically diagnosed RDS. Methods: Twenty calves were instilled intratracheally with bovine lung surfactant extract and provided with standard treatment for RDS (surfactant group). Seven calves were given only standard care for RDS without surfactant therapy and placed in the control group. Standard treatment for newborn calves with RDS includes warming, administration of intranasal oxygen, fluid replacement, administration of antibiotics, and immunoglobulin solution. Arterial blood samples were collected from the calves at 3 observation points, the first just before treatment (hour 0) and at 2 hours (hour 2) and 24 hours (hour 24) after treatment was started to determine if ventilation was adequate, improving, or deteriorating. Blood gases, pH, bicarbonate, and lactate concentrations were measured. Results: In the surfactant group, mean partial pressure of oxygen significantly increased at hours 2 and 24. Mean partial pressure of carbon dioxide decreased and mean arterial blood pH increased at hour 24 in the surfactant group compared with the control group (P < .05). Of the 20 calves in the surfactant group, 12 survived and 8 died. All 7 calves in the control group died. Conclusions and Clinical Importance: The results of this study suggest that surfactant replacement therapy may reduce neonatal deaths in premature calves with clinically diagnosed RDS.
Keywords: blood gases; calf; hyaline membrane disease; lung maturity; neonate; preterm